Relationship of the Built Environment on Nursing Communication Patterns in the Emergency Department: A Task Performance and Analysis Time Study. - Tindle, Kailey; David, Allison; Carlisle, Stephanie; Faircloth, Billie; Fields, J. Matthew; Hayden, Geoffrey; Ku, Bon (Journal of Emergency Nursing, 2020)
The physical layout of the emergency department affects the way in which patients and providers move within the space and can cause substantial changes in workflow and, therefore, affect communication patterns between providers. There is no 1 ED design that enables the best patient care, and quantitative studies looking at ED design are limited. The goal of this study was to examine how different ED designs, centralized and decentralized, are associated with communication patterns among health care professionals. A task performance, direct observation time study was used. By developing a novel tablet-based digital mapping tool using a cloud-based mapping platform (ArcGIS), data on provider actions and interactions were collected and mapped to a precise location within the emergency department throughout an entire nursing shift. The difference in the duration of nurse-physician interactions between the 2 ED designs was statistically significant. Within the centralized design, nurse-physician interactions totaled 14 minutes and 38 seconds compared with 30 minutes and 11 seconds in the decentralized design (t = 2.31, P = 0.02). More conversations between nurses and physicians occurred inside the patient's room in the decentralized design. Our findings suggest that the ED design affects communication patterns among health care providers and that the design has the potential to affect the quality of patient care.